Influence of plaque control on the relationship between rheumatoid arthritis and periodontal health status among Japanese rheumatoid arthritis patients. Issue 9 (14th August 2018) - Hashimoto, Hiroko; Hashimoto, Shimpei; Muto, Akinori; Dewake, Nanae; Shimazaki, Yoshihiro
Abstract: Background: Functional disability of the finger joints in rheumatoid arthritis (RA) patients could affect their oral hygiene and periodontal status because of poor plaque control. We examined the influence of plaque control on the relationship between the severity of RA and periodontal status in RA patients. Methods: This study recruited 89 Japanese RA patients who reported no difficulty in performing oral hygiene. We assessed RA severity using four indices: the Steinbrocker stage and class, the Health Assessment Questionnaire (HAQ) and the Disease Activity Score (DAS). Probing depth (PD), clinical attachment level (CAL), and bleeding on probing (BOP) were taken as parameters of periodontal status. Oral hygiene status was assessed using the plaque index (PlI). We examined the association between the severity of RA and periodontal parameters using multivariable linear regression analyses. Results: In multivariable linear regression analyses not including PlI, Steinbrocker stage III–IV patients had significantly higher PlI scores and greater PD compared with those of stage I. The class III–IV patients had significantly higher PlI scores and greater PD. Patients with an HAQ score ≥0.5 had a significantly higher PlI score than those with an HAQ score of 0. However, when PlI was added to each multivariable model as an independent variable, no significant relationship between RA severity and periodontal status was observed. Conclusions: This study suggests that it is important to consider the influence of plaque control when assessing the relationship between RA severity and periodontal health status in RA patients.